Effects of financial development, institution and financial inclusion on sectoral output, firm and income inequality - Lee, Huay Huay (2020)
This thesis combines three empirical and theoretical chapters on the relationship between various microeconomic and macroeconomic variables and aims to answer three questions: First, are financial development and institution significant in determining sectoral output? Second, are financial development and institution significant in influencing firm’s external financing or growth opportunities in determining firm growth? Finally, what are the relationship between financial inclusion, financial developments, financial institutions and income inequality? In general, this study aims to examine the effects of financial development and institutions on sectoral output, firm and income inequality. The first objective of this thesis is motivated by theoretical and empirical arguments (Robinson, 1952 and Lucas, 1998) amongst the economists of the earlier school of thought asserts that financial development plays a limited role in promoting development of real activity. In contrary, Bagehot (1873), Schumpeter (1911), MacKinnon (1973) and Levine (1997) firmly support the causality linkages from finance to economic development and in later stage only then financial development leads on to growth. In more specific, this study first using dynamic panel system generalized method of moments (GMM) estimation (Blundell and Bond, 1998) to test the annual data covering from 1996 to 2013 for 74 countries - services sector, manufacturing sector and agriculture sector value-added as dependent variable to determine if financial development and institutions play a role in promoting sectoral output. A dynamic system GMM approach is employed to address the endogeneity and serial correlation concern. Findings suggested financial development positively promoting service sector in all countries of different income levels except for upper middle income countries. Institutions are found to have positive role in promoting services sector except in high income level countries. In contrast, financial development and institutions are negatively linked to agricultural sector growth, suggesting possibility of crowding-out effect. The results for manufacturing sector are mixed and inconclusive across countries at different income levels. The policy implications are rather clear, government or policymakers must uphold and strengthen financial structure and development of institutions in order to effectively channel finance resources to productive sectors and raising their sectors’ value-added in countries experiencing greater competition for funds for more expansion and growth. The second objective is motivated by Modigliani and Miller’s (1958) financing constraints theory (FCT) and others like Rajan and Zingales (1998), Fisman and Love (2007), and Manganelli and Popov (2013) also sharing similar enthusiasm that firm growth are dependence on access to external finance but subject to macroeconomic environment. Using firm-level data from firms listed in Bursa Malaysia for 2006-2014 period, the study applies system GMM to estimate how a country’s embedded financial development and institutional quality impacts the linkage of firms’ external financial dependence and growth opportunities to firm growth. Firms which have greater growth opportunities actually grow faster with better financial development with embedded good institutions in the case of Malaysia. So findings concluded that firms experience higher growth through better allocation of finance since they have good potential to grow. This has shed important lights to policymakers in formulating the design of many financial development policies across a wide set of countries aimed at fostering financial markets and banking services sector to provide the vital sources of external financing needed by corporations in financing their investments. A wellfunctioning financial systems is a necessary condition for promoting firm growth. Finally, the third of objective of the study is motivated by Law et al. (2014) that noted financial development decreasing income inequality after certain threshold of institutional quality and new evidence of the role financial inclusion as the main key in reducing income inequality (Garcia-Herrero and Turegano, 2015; Park and Mercado, 2015; de Haan and Sturm, 2016) and this study aims to provide some empirical evidence on the relationship between the three variables. Specifically, this study examines using system GMM for 54 countries over the 2004 – 2010 period from the Standardized World Income Inequality Database (SWIID) and also financial inclusion index by Sarma (2008). Financial inclusion directly has narrowing effect on income inequality when their relationship is assumed linear. However, findings significantly have proven existence of nonlinear U-shaped relationship between financial inclusion both in the presence or without the presence of institutions. Summing up, upholding and strengthening the institutions is a necessary condition and should be strongly noted by policy makers who aspire in using financial inclusion as strategy for fighting income inequality.